Keeping time in the lamina terminalis: Novel oscillator properties of forebrain sensory circumventricular organs. Issue 1 (28th November 2019) - Northeast, Rebecca C.; Chrobok, Lukasz; Hughes, Alun T. L.; Petit, Cheryl; Piggins, Hugh D.
Abstract: Drinking behavior and osmotic regulatory mechanisms exhibit clear daily variation which is necessary for achieving the homeostatic osmolality. In mammals, the master clock in the brain's suprachiasmatic nuclei has long been held as the main driver of circadian (24 h) rhythms in physiology and behavior. However, rhythmic clock gene expression in other brain sites raises the possibility of local circadian control of neural activity and function. The subfornical organ (SFO) and the organum vasculosum laminae terminalis (OVLT) are two sensory circumventricular organs (sCVOs) that play key roles in the central control of thirst and water homeostasis, but the extent to which they are subject to intrinsic circadian control remains undefined. Using a combination of ex vivo bioluminescence and in vivo gene expression, we report for the first time that the SFO contains an unexpectedly robust autonomous clock with unusual spatiotemporal characteristics in core and noncore clock gene expression. Furthermore, putative single‐cell oscillators in the SFO and OVLT are strongly rhythmic and require action potential‐dependent communication to maintain synchrony. Our results reveal that these thirst‐controlling sCVOs possess intrinsic circadian timekeeping properties and raise the possibility that these contribute to daily regulation of drinking behavior.